Calcium-Activated Chloride Channel ANO1/TMEM16A: Regulation of Expression and Signaling - Dulin, Nickolai O. (Frontiers in Physiology, 2020)
Anoctamin-1 (ANO1), also known as TMEM16A, is the most studied member of anoctamin family of calcium-activated chloride channels with diverse cellular functions. ANO1 controls multiple cell functions including cell proliferation, survival, migration, contraction, secretion, and neuronal excitation. This review summarizes the current knowledge of the cellular mechanisms governing the regulation of ANO1 expression and of ANO1-mediated intracellular signaling. This includes the stimuli and mechanisms controlling ANO1 expression, agonists and processes that activate ANO1, and signal transduction mediated by ANO1. The major conclusion is that this field is poorly understood, remains highly controversial, and requires extensive and rigorous further investigation.